Labour quality in Indian manufacturing: a state level analysis - Aggarwal, Suresh Chand (2004)
This paper provides the educational composition of manufacturing workers in 18 states of India during the last four NSSO rounds on employment and unemployment, covering the period 1983 to 1999-2000. It finds that manufacturing workers are more literate today than they were in 1983. It also presents a labour quality index based on the Jorgenson, Gallop, and Fraument methodology for both the rural and urban sectors of the states. The labour quality indices show that quality changes have been quite slow and there is a lot of variation among states in both the rural and urban sectors. The association of the labour quality index with the state's characteristics is found to be weak, but the urban labour quality index has stronger links with the human development index of the states, urban poverty ratio of the state, number of ITIs, and the intensity of industrialisation. - Reproduced.
Keywords: Manufacturing industry - India; Manpower planning - India; Education and employmen - India; Labour - India; Labour